Managing risky assets – mitophagy in vivo - Narendra, Derek P. (Journal of cell science, 2021)
Mitochondria, which resemble their α-proteobacteria ancestors, are a major cellular asset, producing energy ‘on the cheap’ through oxidative phosphorylation. They are also a liability. Increased oxidative phosphorylation means increased oxidative stress, and damaged mitochondria incite inflammation through release of their bacteria-like macromolecules. Mitophagy (the selective macroautophagy of mitochondria) controls mitochondria quality and number to manage these risky assets. Parkin, BNIP3 and NIX were identified as being part of the first mitophagy pathways identified in mammals over a decade ago, with additional pathways, including that mediated by FUNDC1 reported more recently. Loss of Parkin or PINK1 function causes Parkinson's disease, highlighting the importance of mitophagy as a quality control mechanism in the brain. Additionally, mitophagy is induced in idiopathic Parkinson's disease and Alzheimer's disease, protects the heart and other organs against energy stress and lipotoxicity, regulates metabolism by controlling mitochondrial number in brown and beige fat, and clears mitochondria during terminal differentiation of glycolytic cells, such as red blood cells and neurons. Despite its importance in disease, mitophagy is likely dispensable under physiological conditions. This Review explores the in vivo roles of mitophagy in mammalian systems, focusing on the best studied examples – mitophagy in neurodegeneration, cardiomyopathy, metabolism, and red blood cell development – to draw out common themes.